Dynamic characteristics and model optimization of gas adsorption in loaded coal - Jiangwei YAN; Tianke RONG; Xiang FENG; Rui SUN; Juntong LI (Meikuang Anquan)
With the deep extension of coal mine mining, the influence of ground on occurrence state and regularity of coal seam gas is more and more obvious. In order to better study the kinetic characteristics of gas adsorption in the loaded coal, isothermal adsorption experiments were carried out in coal samples under different confining pressures and axial pressures. The quasi-first-order, quasi-second-order, Elovich and Banghamadsorption kinetic models were used to fit and analyze the experimental results, and the adsorption kinetic characteristics and influence mechanism of loaded coal were discussed. It provides a theoretical basis for further exploration of gas occurrence state and law in deep coal seam. Results indicate that as the adsorption progresses, the adsorption capacity increases and the trend gradually slows down and the rate of change of gas adsorption capacity is gradually reduced. The larger the applied load is, the smaller the equilibrium adsorption capacity of gas is. Among the four adsorption kinetic models, the Bangham kinetic model can better describe the dynamic characteristics of coal gas adsorption under the influence of confining pressure, and the quasi-first-order adsorption kinetic model can better describe the dynamic characteristics of coal gas adsorption under the influence of axial pressure. The equilibrium adsorption capacity parameter has a negative power function relationship with confining pressure and axial pressure. The adsorption rate parameters are negatively correlated with the applied load.